Integrated distribution systems planning to improve reliability under load growth - Ziari, I.; Ledwich, G.; Ghosh, Arindam; Platt, G. (IEEE Power Engineering Society, 2012)
Abstract—In this paper, an integrated methodology is proposed for planning distribution networks in which the operation of distributed generators (DGs) and cross-connections (CCs) is optimally planned. Distribution lines and high-voltage/medium-voltage (HV/MV) transformers are also optimally upgraded in order to improve system reliability and to minimize line losses under load growth. An objective functionis constituted, composed of the investment cost, loss cost, and reliability cost. The energy savings that result from installing DGs is also included in this function. The bus voltage and line currentare maintained within their standard bounds as constraints. DG output power is used as another constraint, where this should not be less than 30% of the generator’s rated power; otherwise,the unit is not switched on. The modified discrete particle swarm optimization (PSO) method is employed in this paper for optimizing this planning problem. To evaluate the proposed approach,the distribution system connected to bus 4 of the Roy Billinton test system is used. Four different scenarios are assessed. In the first scenario, a basic planning approach is studied. In thesecond scenario, the use of DG is planned to avoid the line and transformer upgrading. In the third scenario, CC-based planning is studied when no DG exists. Finally, the proposed technique, inwhich all technologies are included, is investigated in the fourth scenario. The outcomes demonstrate that the lowest cost plan results when all technologies are incorporated as proposed in this paper. A study is performed to evaluate the accuracy and robustness of the proposed PSO-based optimization method. The results highlight the applicability of this method for solving the distribution network planning problem.